Răspuns :
Răspuns:
[tex]\bf \: a = {3}^{92}[/tex]
Explicație pas cu pas:
Salutare!
[tex] \bf \: a = {27}^{31} - 2 \cdot {9}^{46} [/tex]
[tex] \bf \: a = ({ {3}^{3} })^{31} - 2 \cdot ({ {3}^{2} })^{46} [/tex]
[tex] \bf \: a = {3}^{3 \cdot31} - 2 \cdot {3}^{2\cdot46} [/tex]
[tex]\bf \: a = {3}^{93} - 2 \cdot {3}^{92} [/tex]
[tex]\bf \: a = {3}^{92} \cdot( {3}^{93 - 92} - 2 \cdot {3}^{92 - 92})[/tex]
[tex]\bf \: a = {3}^{92} \cdot( {3}^{1} - 2 \cdot {3}^{0})[/tex]
[tex]\bf \: a = {3}^{92} \cdot( 3 - 2 \cdot 1)[/tex]
[tex]\bf \: a = {3}^{92} \cdot( 3 - 2)[/tex]
[tex]\bf \: a = {3}^{92} \cdot1[/tex]
[tex] \boxed{\bf \: a = {3}^{92}}[/tex]
==pav38==